An integrated delivery system (IDS) for the management of audiological services in Malaysia - Zaleha A. S.; Cila U. (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2000)
Healthcare integrated delivery system (IDS) is a network of health care services that take into consideration of having a comprehensive information system about patients’ health, health delivery channels and the overall managerial and operational system of the organization. This paper proposed collaboration between the government and private sectors in implementing the concept of IDS to manage audiological services in Malaysia. The primary goal of using this concept is to provide a better management for the hearing-impaired people in Malaysia,especially in children. By using the IDS model, it is hoped that hearing problems will be detected as early as possible, thus resulting in early intervention programs for the hearing-impaired.